211 Subthalamic Nucleus Deep Brain Stimulation Engages Memory Networks in Patients With Parkinson's Disease. (April 2023) - Talati, Pratik; Neudorfer, Clemens; Kratter, Ian; Jorge, Ahmed; Henry, Luke; Horn, Andreas; Richardson, Robert Mark
Abstract : INTRODUCTION: Parkinson's disease (PD) patients with deep brain stimulation (DBS) implantation to the subthalamic nucleus (STN) often have neurocognitive side effects, but the modulated networks associated with their occurrence are largely unknown. METHODS: We localized electrodes and investigated brain connectivity seeding from stimulation volumes in patients that underwent subthalamic deep brain stimulation using a normative resting state functional connectome atlas composed of 1000 healthy subjects. Pre- and post-operative neuropsychological testing data was acquired before and after surgery using two similar memory paradigms (list recall and figure recall). The connectivity profiles associated with changes in these tests were calculated. Results were compared with automated meta-analysis maps calculated using neurosynth and neuroquery. RESULTS: 41 patients were included in the analysis. Positive functional connections between stimulation sites and medial temporal lobe, medial prefrontal cortex, and parieto-occipital region were associated with improvement in list recall. This connectivity profile showed robustness in a leave-one-out cross-validation (R = 0.32, p = 0.027). A similar connectivity profile was associated with figure recall improvement, also robust to cross-validation (R = 0.30, p = 0.019). The profiles associated with the two tasks were able to cross-estimate performance on the respective other task (R = 0.45, p = 0.008; R = 0.26, p = 0.045). When comparing these connectivity profiles with meta-analytic maps in the neurosynth database, the cognitive terms involved with memory showed highest improvement. The neuroquery database areas of predicted activation overlapped with the connectivity maps in the midbody and posterior hippocampal region. CONCLUSIONS: This retrospective study relates modulation of brain networks associated with memory processing with improvements in two separate memory tasks.